MODEL DEVELOPMENT STRATEGY LEARNING 5MT (SQRACT) DIMENSIONS BASED PROCESS FOR ENHANCING COGNITIVE ABILITY TO READ THE SCIENTIFIC DISCOURSE UNDERSTANDING CLASS X SENIOR HIGH SCHOOL - Rina Andriani; Yeti Mulyati (Journal Of Educational Experts (JEE), 2019)
This study aims to develop and test the effectiveness of the strategy learning model 5MT (mengamati, menanya, membaca, menalar, mengomunikasikan, tes) (SQRACT= survey, question, read, association, communicating, test)) based on the dimension of the cognitive processes to improve reading comprehension of scientific discourse. The study was conducted using the method Reseacrh & Development, includes three phases: the planning, the development, and implementation stages.The implementation results showed among a control group with the experimental group, there is a significant difference of 0.005 <0.05. While learning to read when they see the results of scientific discourse  understanding gained significant difference of 0.009 <0.05 between  who have high scientific attitude and students who have low scientific attitude, and if the relationship between reading comprehension of scientific discourse with a scientific attitude is not there a significant relationship 0.985>0.05. Thus the authors  can improve reading comprehension while enhancing the ability to think of High Order Thinking class X SMAN Ciparay Bandung regency in the academic year 2015/2016